2021
DOI: 10.20944/preprints202105.0705.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-Fire Susceptibility to Brittle Fracture of Selected Steel Grades Used in Construction Industry – Assessment Based on the Instrumented Impact Test

Abstract: The change in the value of the breaking energy is discussed here for selected steel grades used in building structures after subjecting the samples made of them to episodes of heating in the steady-state heating regime and then cooling in a simulated fire conditions. These changes were recorded based on the instrumented Charpy impact tests, in relation to the material initial state. The S355J2+N, 1H18N9T steels and also X2CrNiMoN22-5-3 duplex steel were selected for detailed analysis. The fire conditions were … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…This in turn induced higher susceptibility to brittle fracture. These conclusions seem to be in complete agreement with results of earlier research conducted by the authors, reported in the papers [6][7][8].…”
Section: Results Obtained On Samples Made Of S355j2+n Steelsupporting
confidence: 93%
See 1 more Smart Citation
“…This in turn induced higher susceptibility to brittle fracture. These conclusions seem to be in complete agreement with results of earlier research conducted by the authors, reported in the papers [6][7][8].…”
Section: Results Obtained On Samples Made Of S355j2+n Steelsupporting
confidence: 93%
“…In particular, it is not so much about the a posteriori observation of the complete lack of susceptibility to initiate brittle cracks in the tested material, but about the observed post-fire loss of the capability to effectively arrest the unrestrained growth of such cracks. This paper constitutes a continuation of previous works published earlier in [6][7][8].…”
Section: Introductionsupporting
confidence: 56%